Pediatric CNS Tumors - Gupta, Nalin; Banerjee, Anuradha; Haas-Kogan, Daphne; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Pediatric CNS Tumors is a detailed review of childhood brain tumors with a particular emphasis on providing treatment algorithms for each tumor type. Controversies and current therapeutic agents under development are also discussed. The second edition includes expanded chapters on embryonal tumors, rare tumor types, and supportive care for patients with brain tumors.
Low-Grade Gliomas -- High-Grade Gliomas -- Brainstem Gliomas -- Ependymoma -- Embryonal Tumors -- Intracranial Germ Cell Tumors -- Craniopharyngioma -- Neuronal Tumors -- Choroid Plexus Tumors -- Intramedullary Spinal Cord Tumors -- Rare Tumors -- Neurocutaneous Syndromes and Associated CNS Tumors -- Modern Neuroimaging of Pediatric Brain Tumors -- Current Surgical Management -- Chemotherapy -- Advances in Radiation Therapy -- Late Effects of Treatment and Palliative Care.
Keywords: Medicine; Radiotherapy; Neurology; Neurosurgery; Oncology; Pediatrics; Medicine & Public Health; Oncology; Pediatrics; Neurology; Neurosurgery; Radiotherapy